Pengaruh Positioning Produk Dan Differensiasi Produk Terhadap Citra Merek Pada Produk Ban Accelera - ., Sujana; Nurendah, Yulia; Wirakusuma, Ilham (Jurnal Ilmiah Manajemen Kesatuan, 2016)
Currently, the mastery of increasingly sophisticated technologies in the enterprise is required as a condition to solve complex problems (advanced) because of the tight competition in the free market, the competition will drive systems in Indonesia's economy to a free market and positioned marketers to always develop products and capture market share. In seizing market share, causing competition among companies, a marketer is required to always develop a marketing strategy. One strategy used is the product positioning and product differentiation, this is done to attract customers and give satisfaction to the consumer that leads to branding. This study aims to determine the effect of Product Positioning and Product Differentiation on Brand Image of Accelera Tires products. This study is a description of the survey approach. Retrieval of data is using questionnaires with respondents of 100 subscribers of PT. Elangperdana Tyres Industry. The results showed that the relationship of the product positioning of the brand image is at .749 and contributed 56 percent to the image of the brand and product differentiation variable relationship to the brand image is 0.715 and accounted for 51.1 percent. Influence between product positioning and product differentiation to the brand image known that multiple correlation regression analysis regression coefficients Product Positioning (X1 = 0.629), and the Product Differentiation regression coefficient (X2 = 0.389) and contributed 59.4 percent. Analysis of the correlation coefficient is 0.770 Brand image variables indicate a strong relationship between the independent variable on the dependent variable that is equal to 77 percent. It can be concluded that the product positioning and product differentiation affect the brand image. This is evident from the contribution of a given variable product positioning and product differentiation to the brand image.